Evaluating the role of inter-societal interaction in the emergence of institutionalized hierarchy : an example from Southern Ecuador - Taylor, Sarah R. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
Inter-societal interaction has been a popular topic in Andean archaeology from its inception. Long distance trade, vertical reciprocity, state expansion, core-periphery relations, and the spread of ideological constructs have been persistent topics in the region. The importance of inter-societal interaction in the modern history of the Andes leaves little wonder that archaeologists are interested in the role such interactions might have played in prehistory.

La interacción entre sociedades ha sido un tema recurrente en la arqueología andina desde sus inicios. El comercio a larga distancia, la reciprocidad vertical, la expansión estatal, las relaciones centroperiferia, y la diseminación de onstrucciones ideológicas han sido temas persistentes en la región. La importancia de la interacción entre sociedades en la historia moderna de los Andes deja poca duda de por qué los arqueólogos se podrían interesar en el rol que dichas interacciones jugaron en la prehistoria.
Páginas 101-125
Keywords: Arqueología--Ecuador; Arqueología--Perú; https://purl.org/pe-repo/ocde/ford#6.01.02